2014
DOI: 10.1634/theoncologist.2014-0130
|View full text |Cite
|
Sign up to set email alerts
|

The Opioid Rotation Ratio of Hydrocodone to Strong Opioids in Cancer Patients

Abstract: Purpose. Cancer pain management guidelines recommend initial treatment with intermediate‐strength analgesics such as hydrocodone and subsequent escalation to stronger opioids such as morphine. There are no published studies on the process of opioid rotation (OR) from hydrocodone to strong opioids in cancer patients. Our aim was to determine the opioid rotation ratio (ORR) of hydrocodone to morphine equivalent daily dose (MEDD) in cancer outpatients. Patients and Methods. We reviewed the records of consecutive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
18
1
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 51 publications
1
18
1
1
Order By: Relevance
“…This is consistent with previous findings in which hydrocodone was identified as the most frequently prescribed and abused opioid . It was traditionally considered a weak opioid, but several studies have indicated that it may be equally as potent as morphine or oxycodone . In view of the significant potential for its abuse, in October 2014, the US Drug Enforcement Agency recategorized hydrocodone as a Schedule 2 drug, hence increasing the level of scrutiny and caution regarding its prescription by clinicians.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is consistent with previous findings in which hydrocodone was identified as the most frequently prescribed and abused opioid . It was traditionally considered a weak opioid, but several studies have indicated that it may be equally as potent as morphine or oxycodone . In view of the significant potential for its abuse, in October 2014, the US Drug Enforcement Agency recategorized hydrocodone as a Schedule 2 drug, hence increasing the level of scrutiny and caution regarding its prescription by clinicians.…”
Section: Discussionmentioning
confidence: 99%
“…61 It was traditionally considered a weak opioid, 62 but several studies have indicated that it may be equally as potent as morphine or oxycodone. [63][64][65][66][67][68] In view of the significant potential for its abuse, in October 2014, the US Drug Enforcement Agency reca-tegorized hydrocodone as a Schedule 2 drug, [69][70][71] hence increasing the level of scrutiny and caution regarding its prescription by clinicians. Our findings support the appropriateness of this decision.…”
Section: Discussionmentioning
confidence: 99%
“…The possible occurrence of hyperalgesia with high doses of opioids has been previously reported. 35,43 It is important to note that the sample size of patients receiving >30 mg of IV hydromorphone/ day was very small. Further prospective studies should try to confirm this finding.…”
Section: Discussionmentioning
confidence: 99%
“…The MEDD was calculated using standard ORRs 42 ; an ORR of 5.0 was used to calculate the MEDD of methadone, 46 and 1.5 was used to calculate the MEDD of hydrocodone. 44 The net MEDD was used for calculation of the ORR from other strong opioids to TDF. Net MEDD is the MEDD before OR minus the MEDD of the breakthrough opioid used along with TDF after OR.…”
Section: Calculation Of the Tdf Dose And Net Meddmentioning
confidence: 99%